Impact of multifaceted interventions on pressure injury prevention: a systematic review - Usha Rani Kandula (BMC Nursing)
Abstract Background Pressure injuries are a significant concern in healthcare settings, leading to increased morbidity, healthcare costs, and patient suffering. This systematic review aims to evaluate the impact of multifaceted interventions on the prevention of Pressure injuries and improvements in nursing practices. Methods A systematic search was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines across multiple databases, including studies from Google Scholar (332), Science Direct (14), grey literature sources (45), PubMed (0), Cochrane Library (437), and Hinari (322). Studies included in the review examined the effectiveness of various interventions, including educational programs, care bundles, and positioning strategies, on Pressure injury prevention. Results The interventions significantly reduced Pressure injury prevalence from 60.9 to 28.7%, with hospital-acquired injuries decreasing from 52.9 to 21.3%. The mean national prevalence of Pressure injuries was 17.6%, with 58.1% being community-acquired. Educational programs greatly enhanced nurses’ knowledge and practices, particularly regarding the Braden scale and wound care protocols. Key risk factors identified were patient age, sex, and chronic diseases. Effective strategies included the use of air cushions and specific positioning techniques. Care bundles were found to prevent pressure ulcers in 90% of patients in the study group, and medical device-related Pressure Injuries were reduced to 5.01%. Conclusion Multifaceted interventions, including education, care bundles, and positioning strategies, are highly effective in reducing the prevalence of Pressure Injuries and improving nursing practices. Implementing comprehensive prevention strategies is essential for mitigating Pressure Injury risks in healthcare settings.